Moderinisasi Pelaksanaan Pendidikan Agama Kristen Disekolah Termarginal - Yosua Dwi Noriyanto (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2026)
The modernisation of education in the 21st century requires the integration of technology, participatory approaches, and social justice as the foundation for relevant and contextual learning in various disciplines, including Christian Religious Education. In the Indonesian context, these changes have not been evenly distributed, especially in schools located in marginalised socio-economic conditions. Christian Religious Education in these areas still faces limitations in terms of facilities, a lack of digital pedagogical competence, and a gap between theological ideals and the social reality of students. The phenomenon that has emerged shows that the implementation of Christian Religious Education in marginalised schools tends to be administrative in nature, lacking in dialogue, and failing to touch on the concrete experiences of students' lives in a reflective manner. This study aims to analyse the modernisation process of Christian Religious Education implementation in marginalised schools from the perspective of social constructivism and theology of justice. The method used is a descriptive qualitative approach, which concludes that context-based and simple digital pedagogical transformation strengthens the relevance of learning in marginalised schools through a participatory and reflective approach. The negotiation of the meaning of faith affirms spirituality that arises from experiences of suffering and social resilience. The modernisation of Christian Religious Education from a social constructivism perspective shapes dialogical learning that builds contextual faith. The integration of theological and social justice dimensions presents a liberating practice of faith, encourages solidarity, and strengthens students' ethical awareness in complex realities of life.AbstrakModernisasi pendidikan abad ke-21 menuntut integrasi teknologi, pendekatan partisipatif, serta keadilan sosial sebagai landasan pembelajaran yang relevan dan kontekstual dalam berbagai disiplin, termasuk Pendidikan Agama Kristen. Dalam konteks Indonesia, perubahan tersebut belum terdistribusi secara merata, khususnya pada sekolah-sekolah yang berada dalam kondisi sosial dan ekonomi marginal. Pendidikan Agama Kristen di wilayah tersebut masih menghadapi keterbatasan sarana, minimnya kompetensi pedagogis digital, serta kesenjangan antara idealitas teologis dan realitas sosial peserta didik. Fenomena yang muncul menunjukkan bahwa pelaksanaan PAK di sekolah marginal cenderung bersifat administratif, kurang dialogis, dan belum menyentuh pengalaman konkret kehidupan peserta didik secara reflektif. Penelitian ini bertujuan untuk menganalisis proses modernisasi pelaksanaan Pendidikan Agama Kristen di sekolah termarginal dalam perspektif konstruktivisme sosial dan teologi keadilan. Metode yang digunakan adalah pendekatan kualitatif deskriptif dapat disimpulkan bahwa transformasi pedagogis berbasis konteks dan digital sederhana memperkuat relevansi pembelajaran di sekolah marginal melalui pendekatan partisipatif dan reflektif. Negosiasi makna iman menegaskan spiritualitas yang lahir dari pengalaman penderitaan dan ketahanan sosial. Modernisasi PAK dalam perspektif konstruktivisme sosial membentuk pembelajaran dialogis yang membangun iman kontekstual. Integrasi dimensi teologis dan keadilan sosial menghadirkan praksis iman yang membebaskan, mendorong solidaritas, serta memperkuat kesadaran etis peserta didik dalam realitas hidup yang kompleks.